2021
DOI: 10.1002/elps.202100154
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity assessment of dairy products by capillary electrophoresis

Abstract: Authenticity assessment of dairy products by capillary electrophoresisMilk and derivatives are a very important part in the diet of the world population. Products from goat, buffalo, and sheep species have a greater economic value than the cow ones, therefore, authenticity frauds by improperly adding cow's milk occur frequently: dairy products are among the seven more attractive foods for adulteration. Milk from each of the above-cited animal species has its own definite profile of whey proteins (variants of α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 128 publications
0
10
0
Order By: Relevance
“…However, large protein aggregates fail to migrate into the gel and the analysis only provides a semi-quantitative estimation [ 28 , 29 ]. Recent applications reported by literature support the reliability of CZE under reducing conditions in the separation of both native and denatured whey proteins [ 25 , 30 , 31 ], although the incomplete solubilization of large aggregates may also represent a limitation with this technique, as discussed below. Liquid chromatography mass spectrometry methods based on a multiple reaction monitoring approach were recently proposed for the quantification of several milk proteins simultaneously [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, large protein aggregates fail to migrate into the gel and the analysis only provides a semi-quantitative estimation [ 28 , 29 ]. Recent applications reported by literature support the reliability of CZE under reducing conditions in the separation of both native and denatured whey proteins [ 25 , 30 , 31 ], although the incomplete solubilization of large aggregates may also represent a limitation with this technique, as discussed below. Liquid chromatography mass spectrometry methods based on a multiple reaction monitoring approach were recently proposed for the quantification of several milk proteins simultaneously [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…CE-UV and CE off-line coupled with LC-MS/MS were utilized for the analysis of human milk proteins [199]. CE was found to be an appropriate method for the analysis of milk proteins and the assessment of the authenticity of dairy products [200][201][202].…”
Section: Food Analysismentioning
confidence: 99%
“…Along with a comprehensive book collection that provides an interesting assembly of articles devoted to facing challenges related to food quality, safety, and interactions food‐health from a Foodomics perspective [9], other review works devoted to the application of CE for food analysis [18] or their specific coupling to mass spectrometry (MS) for metabolomics [13, 14] or food analysis [10] have also been published. The most recent applications of CE to the analysis of amino acids (AAs) [12], peptides and proteins [22], acrylamide [19], or dairy products [21] as well as its use in chiral analysis [16] or for the proteomics characterization of food‐derived bioactive peptides [15] have also been recently reviewed. Moreover, different reviews focused on the potential of microchip electrophoresis for the analysis of foodstuffs and beverages [11], pathogenic bacteria and viruses [17], or peptides [20] have been published.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this analytical technique can nowadays be considered a powerful tool in this topic as it has been highlighted by our previous review papers published in Electrophoresis since 2006 [1][2][3][4][5][6][7][8]. The high potential of CE in this field has given rise to a considerable number of review articles as it is demonstrated by Table 1, which summarizes the main reviews published within the period covered by the present work on the application of CE methods in food analysis and Foodomics [9][10][11][12][13][14][15][16][17][18][19][20][21]. Along with a comprehensive book collection that provides an interesting assembly of articles devoted to facing challenges related to food quality, safety, and interactions food-health from a Foodomics perspective [9], other review works devoted to the application of CE for food analysis [18] or their specific coupling to mass spectrometry (MS) for metabolomics [13,14] or food analysis [10] have also been published.…”
Section: Introductionmentioning
confidence: 99%